(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2023)
A brief introduction to a new model for online archiving and journal publishing that rejects a print lineage (book or magazine) for online publication but rather embraces a screen-based genealogy, foregrounding both cinematic and gaming approaches to digital design, user experience and navigation. Visit www.herri.org.za.